Rendimiento académico de un niño de 12 años e incidencia en el bienestar psicológico de los padres en la Unidad Educativa Emigdio Esparza Moreno - Vistín Orta, Magali Mercedes (2021)
In the present Case Study it is exposed how the poor academic performance of the child directly affects the psychological well-being of the parents, emphasizing the well-being of the mother who is the one with whom he interacts the most, since his father, due to his work situation, remains absent. , the present study proposes to determine the incidence using tools such as the Clinical History, the Beck Anxiety Inventory (BAI) and the Carol Ryff Psychological Well-being Scale under the criteria indicated by the DSM - 5, the diagnosis of this patient is another unspecified anxiety disorder 300 (F41.9), since it does not meet all the criteria, and thus it was possible to carry out an outline of the psychotherapeutic process based on cognitive-behavioral therapy in order to modify behaviors that affect well-being parental psychological